MICRO SMALL BUSINESS LICENSE SERVICES COLLABORATIVE GOVERNANCE IN NORTH JAKARTA ADMINISTRATIVE CITY - Lesmana, Dina; Sumiati, Nia (Jurnal Darma Agung; Vol 29 No 2 (2021): AGUSTUSDO - 10.46930/ojsuda.v29i2.2334, 2021)
The goal of this study is to identify collaborative governance in micro and small business licensing services in the Administrative City of South Jakarta, as well as how the ideal collaborative governance model is provided in Micro Small Business Licensing Services (IUMK). This is a descriptive qualitative study in which data was gathered through in-depth interviews, observation, and documentation. According to the study's findings, the concept of Collaborative Governance provided has eight dimensions: (1) Network structure: network structure that allows active participation in the network, network structure that is not hierarchical but tends to be flat and non-monopolistic; (2) Commitment to common goals: the government's commitment to providing simple, quick, and transparent services; (3) Participant Trust: Public/applicant trust must be strengthened, particularly during the implementation phase. The implementation of the Collaborative Governance concept is expected to accelerate licensing services in every PTSP where this institution is very close to the community, in accordance with the DKI Jakarta Government's goals, vision, and mission.